Importance of drivetrain optimisation to maximise electrical power from wave energy converters - Nataliia Y. Sergiienko; Leandro Souza Pinheiro da Silva; Boyin Ding; Benjamin S. Cazzolato (IET Renewable Power Generation, 2021)
Abstract This article demonstrates the benefits of optimising the drivetrain to improve the level and quality of electrical power output from a wave energy converter. The study considers a spherical buoy connected to a permanent magnet synchronous generator through a mechanical drive. The wave energy converter is equipped with a model predictive control system that maximises electrical power from the generator. Three different scenarios are compared: (i) when the drivetrain is not optimised, (ii) when only the gear ratio is optimised, (iii) and when both gear ratio and flywheel inertia are optimised. The performance of all three configurations is compared in terms of their effect on the generator operating range, the natural frequency of the system, the amount of generated electrical power, and control forces. The results demonstrate that the drivetrain optimisation leads to a significant increase in the electrical power output while shifting the generator's operating range to areas with the highest efficiency. Moreover, drivetrain designs that utilise a flywheel reduce the power take‐off loads and facilitate smoother power production.